Ultrafast acousto-optic mode conversion in optically birefringent ferroelectrics - Mariusz Lejman (Nature Portfolio, 2016)
Electrically driven acousto-optic light modulators are limited to frequencies of a few hundred megahertz and are typically no smaller than a few micrometres. Here, the authors demonstrate gigahertz acousto-optic conversion of light polarization in a region of a few nanometres using pulsed laser stimulation of a ferroelectric.